Gout management using uricase and sodium citrate hollow mesoporous nanomotors - Lu Liu; Xiurong Li; Yongxian Chen; Junbin Gao; Yuejun Jiang; Yicheng Ye; Peng Wang; Fei Peng; Yingfeng Tu (Nature Communications, 2025)
Abstract Uricase (UOx)-based gout treatments are generally limited due in part to the accumulation of H2O2 in an arthrosis environment characterized by a sluggish metabolism. Here we develop a self-cascade nanomotor with high efficiency toward simultaneous uric acid (UA) degradation and H2O2 elimination on the basis of UOx and sodium citrate loading in amine functionalized hollow mesoporous silica nanoparticles (AHMSNs). Due to the inherent asymmetry of AHMSNs, the developed nanomotors can be actuated by ionic diffusiophoresis induced by the enzymatic UA degradation, thus enlarging the diffusion range within the joint cavity. H2O2 generated during UA decomposition can be simultaneously eliminated by the loaded sodium citrate, resulting in a considerable improvement in mammalian cell viability. In vivo studies display powerful therapeutic effect in gouty models using this self-cascade nanomotor system. These results present the potential of nanomotors as active therapeutic agents for gout, providing a perspective on the application of enzyme-driven micro/nanomotors.